Characterizing Molecular Variants and Clinical Utilization of Next-generation Sequencing in Advanced Breast Cancer. Issue 6 (July 2017) - Gurda, Grzegorz T.; Ambros, Tadeu; Nikiforova, Marina N.; Nikiforov, Yuri E.; Lucas, Peter C.; Dabbs, David J.; Lee, Adrian V.; Brufsky, Adam M.; Puhalla, Shannon L.; Bhargava, Rohit
Abstract : Women with advanced breast carcinomas have few therapeutic options. Recent advances in genomic profiling represent a new paradigm of cancer classification and treatment, but experience with genomic testing in a clinical setting remains limited. We retrospectively determined the genomic variants and correlate these with histology [histomorphologic subtype, nuclear grade, standard immunohistochemistry (IHC)] and clinical utilization (ordering, turnaround time, report review, and targeted therapy). Among 48 patients, 2 showed no genetic alterations, 11 (23%) showed variants of unclear significance only and 35 (73%) showed variant(s) affecting function (VaF) and/or variants of unclear significance. Overall, 119 variants were observed in 20 of 50 tested genes. Each patient had a unique molecular profile, with numerous (n=58) variants not previously reported in breast cancer. VaF detected in more than 2 patients included: TP53 (n=21), PIK3CA (n=20), and FGFR1 (n=3). VaF comprised 46 single nucleotide variants (79%), 7 amplifications (12%), 3 frameshifts (5%), 1 insertion (2%), and 1 deletion (2%). The tested samples had very high Ki67 index (average 57%±23%) and approximately half were hormone receptor and HER2 negative (25/46, 54%). Metastatic breast carcinomas showed a higher average VaF versus breast-localized tumors (1.3±0.99 vs. 0.18±0.60, P <0.05). Next-generation sequencing reports were promptly reported and reviewed (average 1 to 2 d) and 7 (∼25%) of potentially eligible patients received targeted therapy. Advanced breast cancers show unique landscapes of genetic variants. Most testing was done in late disease, often in metastatic and receptor-negative carcinomas. Next-generation sequencing results were promptly reported and reviewed, but the utilization of targeted therapies was limited. Abstract : Supplemental Digital Content is available in the text.